The search for sustainable competitive advantage : a stakeholder management perspective : a thesis presented in partial fulfillment of the requirements for the degree of Doctor of Philosophy in Management at Massey University, Albany, New Zealand - Wu, Minyu (Massey University, 2010)
Competitive advantage and stakeholder management are two important research streams that have attracted much attention during the past two decades. Although competitive advantage is the core issue of strategic management in which stakeholder management is rooted, the two topics have developed seemingly independently in the literature. The main purpose of this thesis is to explore how stakeholder management influences competitive advantage. The research is guided by a theoretical framework that employs a stakeholder perspective, linking three perspectives of competitive advantage—the resource-based view, the relational view, and the activity-position view. The general research approach chosen is a qualitative, multiple-case study. Ten cases were selected, from leading firms of several industries in Taiwan, and in-depth interviews were conducted. Results showed that a firm’s competitive advantage comes from its resource capacity (superior resources, unique capabilities, and solid relationships) and a mix of activities that respond to the competitive context. Competitive advantage, too, can be analysed in terms of two components: resource advantage and positional advantage. Stakeholder management can have significant influences on resource advantages as stakeholders play important roles in the process of value creation. They are the providers who supply valued resources to the firm and, as such, can act as catalysts or hindrances that either facilitate or impede the generation of valued resources. Successful stakeholder management strengthens a firm’s resource profile and thus enhances its resource advantages. Stakeholder management also has considerable influences on positional advantages, as stakeholders are relevant to activities and drivers that determine cost and differentiation. Moreover, stakeholders are key players in the competitive context, who help to shape the competitiveness of the firm. The study reported that stakeholder management helps to sustain competitive advantage through advancing a firm’s resource capacity—resource commitment, developing capabilities, and building relationships. Stakeholder management also generates several isolating mechanisms that preserve competitive advantage, including time compression diseconomies, causal ambiguity, social complexity, and transaction costs. However, in the face of ever-changing situations, managers need to adopt different strategies for managing stakeholder relations. To achieve sustained competitive advantage in a dynamic context, firms not only have to strengthen the capacity of resource advantage to fit the competitive strategy, but also need to use innovative and entrepreneurial approaches for managing their stakeholder relations.
Keywords: Strategic management; Taiwan; Fields of Research::350000 Commerce, Management, Tourism and Services::350200 Business and Management